Structural Changes in Economics and their Impact on the Labor Market - Pavlovna, Shelomentseva Valentina; Anatoliyevna, Ifutina Yelena; Anatoliyevna, Frezorger Larisa (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
One of the main goals of social and economic development of the national economy is to improve the quality and standard of living of the population on the basis of realizing the innovative potential of the economy. Currently, the main areas of modernization are the renewal and restructuring of the economy, the creation of competitive products, the inclusion in the world of innovative processes and integration into the world economy, the intensive use of all the major innovations. In the world today, some countries are discovering new opportunities for development, while in others, there is a restriction in development, and this is primarily due to the fact that they are at different stages of the technological order. Modernization of the economy is impossible without the modernization of the labor market, as the development and implementation of development programs for the housekeeper are staffed. Staffing the economy of the country at present is an important socio-economic problem affecting all spheres of economic activity in the country. This problem is caused, first of all, by the quantitative and qualitative discrepancy between the supply and demand of labor. The article describes modern trends in the formation of the labor market, due to the need to move to the Industry 4.0. Factors determining the necessary changes in the labor market in connection with the modernization of enterprises and the transition to a new technological order are considered. The world practice of applying foresight technology as a tool for forecasting and planning the development prospects of the region is considered. Measures have been defined to improve the system of training personnel for modern enterprises. The basic directions on perfection of planning and regulation of a labor market are formulated.